Tuberculosis contact tracing: are the British Thoracic Society guidelines still appropriate? - Hussain, S F (1992)
The value of contact tracing in South Glamorgan for the period May 1987 to December 1989 was assessed. Tuberculosis was diagnosed in six (3.5%) of 170 close contacts. All were young and were detected in the initial screening. Tuberculosis was not found among 441 casual contacts. The value of follow up of contacts after the initial screening and of screening casual contacts in districts with a low prevalence of tuberculosis is questioned.